2019
DOI: 10.1155/2019/2306518
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity Study of the C60-L-Threonine Derivative for Potential Application in Agriculture

Abstract: The present paper reports data on the biological activity of nanocompositions based on a C60-L-threonine (C60-Thr) derivative. These nanocompositions promote the nonspecific resistance of plants to the action of stress factors (ultraviolet radiation, pesticides, and phytopathogens). Additionally, we determined the perspectives of the C60-Thr adduct application in the cultivation of plants due to the decrease of the pesticide load on the environment. The biological study of C60-Thr revealed the plant growth-sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 77 publications
(85 reference statements)
0
16
0
1
Order By: Relevance
“…We know very little if nothing about the mechanisms of potential indirect influence of fullerene derivatives on plants after penetration soil. We were the first to show that increase in net production of plants and their resistance to oxidative stress after introduction of polyhydroxylated, carboxylated and aminoacid derivatives of C 60 in the root-inhabited environment or after foliar treatment of plants is evidently associated with the determined changes in the structure and efficiency of photosynthetic system and with the influence on the metabolic, substance exchange processes in plants, antioxidant protections systems, in particular on lipid peroxidation intensity, superoxide dismutase activity and reactive oxygen intermediate generation [21,[25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…We know very little if nothing about the mechanisms of potential indirect influence of fullerene derivatives on plants after penetration soil. We were the first to show that increase in net production of plants and their resistance to oxidative stress after introduction of polyhydroxylated, carboxylated and aminoacid derivatives of C 60 in the root-inhabited environment or after foliar treatment of plants is evidently associated with the determined changes in the structure and efficiency of photosynthetic system and with the influence on the metabolic, substance exchange processes in plants, antioxidant protections systems, in particular on lipid peroxidation intensity, superoxide dismutase activity and reactive oxygen intermediate generation [21,[25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was discovered that nano-formulated alumina has increased cuticular attachment, which increases the probability of cytotoxicity (Buteler et al, 2018). Some other metallic nanoparticles such as MnO, TiO 2 , Ag, and Fe 3 O 4 have also shown a variety of antifungal activities on a diverse group of fungal pathogens from crops (Chen J et al, 2020;Panova et al, 2019;Paramo et al, 2020;Wang et al, 2017). Besides metallic AIs, some non-metallic AIs like graphene oxide (C 14 0H 42 O 20 ) (Wang et al, 2017; and silicon (Rastogi et al, 2019) are also reported to have an insecticidal response to several pathogens.…”
Section: Active Ingredientmentioning
confidence: 99%
“…This article continues the series of articles investigating the synthesis, identification and properties of fullerenols. Some articles are devoted to the investigation of the influence of water-soluble fullerene derivatives on plants growth and development and common bioactivity (for example [1][2][3][4][5][6][7][8][9][10][11]). The common conclusion in the part, related to the bio-activity of water soluble adducts of light fullerenes on plant is the following -these derivatives have a beneficial effect on grow and development of plants, in any case when using not very high concentrations of the latter -n•10 2n•10 3 g/dm 3 .…”
Section: Introductionmentioning
confidence: 99%